2008
DOI: 10.1128/mcb.01648-07
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Est2p Affects Telomere Length by Influencing Association of Rap1p with Telomeric Chromatin

Abstract: In Saccharomyces cerevisiae, the sequence-specific binding of the negative regulator Rap1p provides a mechanism to measure telomere length: as the telomere length increases, the binding of additional Rap1p inhibits telomerase activity in cis. We provide evidence that the association of Rap1p with telomeric DNA in vivo occurs in part by sequence-independent mechanisms. Specific mutations in EST2 (est2-LT) reduce the association of Rap1p with telomeric DNA in vivo. As a result, telomeres are abnormally long yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…Our previous work showed that mutations in EST2 that cause telomere lengthening are associated with changes in the telomere sequence (Ji et al, 2008). Both est2-LT E76K and est2-up34 [D460N; located within the reverse transcriptase domain (Eugster et al, 2006)] cause the same telomere sequence changes despite requiring different genetic pathways for over-elongation (Ji et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous work showed that mutations in EST2 that cause telomere lengthening are associated with changes in the telomere sequence (Ji et al, 2008). Both est2-LT E76K and est2-up34 [D460N; located within the reverse transcriptase domain (Eugster et al, 2006)] cause the same telomere sequence changes despite requiring different genetic pathways for over-elongation (Ji et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Both est2-LT E76K and est2-up34 [D460N; located within the reverse transcriptase domain (Eugster et al, 2006)] cause the same telomere sequence changes despite requiring different genetic pathways for over-elongation (Ji et al, 2008). Based on these data, it remained possible that telomere sequence changes observed in these est2 mutant strains are an indirect consequence of disrupted telomere length homeostasis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations